Macrobotanic data implementing Forensic Geology investigations - Marina Morabito; Fabio Mondello; Roberta Somma (Atti della Accademia peloritana dei pericolanti. Classe I di scienze fis., mat. e naturali, 2023)
The contribution of botany to the analysis of geological traces should not be neglected in forensic investigations. Small plant traces, especially if widespread in quantity, easily adhere to the subjects involved in criminal events. However, the identification of highly fragmentated plant structures often relies to skilled experts. The present paper deals with the morphological descriptions of thorns and similar plant appendices produced by the plants thriving in the area under investigation in a court case regarding the disappearance of two subjects in a rural area of the countryside. Comparative observations between unknown and known samples, related to victims and crime scene respectively, made it possible to identify traces found on the victims as plants thriving in the area under investigations. Basing on the punctual distribution of individual plants in the investigated territory, the results of the comparative analyses allowed to reconstruct the victims’ path in the hours immediately preceding their death. Consequently, these data provided valuable information for implementing the geological investigation carried out for the judicial authority.